Central blockade of orexin type 1 receptors reduces naloxone induced activation of locus coeruleus neurons in morphine dependent rats. (11th June 2021) - Aghajani, Niloofar; Pourhamzeh, Mahsa; Azizi, Hossein; Semnanian, Saeed
Highlights: Orexin type 1 receptors (OX1Rs) have been reported to be involved in morphine withdrawal. Morphine withdrawal behaviors are associated temporally with LC neuronal hyperactivity. Central blockade of OX1Rs reduces naloxone-induced hyperactivity of LC neurons. Abstract: Orexin neuropeptides are implicated in the expression of morphine dependence. Locus coeruleus (LC) nucleus is an important brain area involving in the development of withdrawal signs of morphine and contains high expression of orexin type 1 receptors (OX1Rs). Despite extensive considerations, effects of immediate inhibition of OX1Rs by a single dose administration of SB-334867 prior to the naloxone-induced activation of LC neurons remains unknown. Therefore, we examined the direct effects of OX1Rs acute blockade on the neuronal activity of the morphine-dependent rats which underwent naloxone administration. Adult male rats underwent subcutaneous administration of 10 mg/kg morphine (two times/day) for a ten-day period. On the last day of experiment, intra-cerebroventricular administration of 10 μg/μl antagonist of OX1Rs, SB-334867, was performed just before intra-peritoneal injection of 2 mg/kg naloxone. Thereafter, in vivo extracellular single unit recording was employed to evaluate the electrical activity of LC neuronal cells. The outcomes demonstrated that morphine tolerance developed following ten-day of injection. Then, naloxone administration causes hyperactivity of LC neuronal cells, whereas a single dose administration of SB-334867 prior to naloxone prevented the enhanced activity of neurons upon morphine withdrawal. Our findings indicate that increased response of LC neuronal cells to applied naloxone could be prevented by the acute inhibition of the OX1Rs just before the naloxone treatment.